The influence of witness intoxication, witness race, and defendant race on mock juror decision making - Ewanation, Logan (Canadian journal of criminology and criminal justice, 2018)
Negative stereotypes about Indigenous people concerning alcoholism and criminality permeate Canadian society. This study primarily explores whether racial bias affects mock jurors' perceptions of Indigenous eyewitnesses, particularly when the eyewitness was intoxicated at the time of the crime. [End Page 505] Participants read a trial transcript in which eyewitness intoxication and both eyewitness and defendant race (Indigenous/white) were manipulated, then provided a verdict and responded to a series of questions about the eyewitness. We found an indirect effect of eyewitness intoxication on verdict, operating through perceived eyewitness accuracy, such that intoxicated eyewitnesses were associated with significantly fewer convictions. Participants also rated Indigenous eyewitnesses as more accurate than white eyewitnesses. Although there were no significant main effects of defendant or eyewitness race on verdicts, we did observe a significant indirect effect of eyewitness race: Indigenous eyewitnesses were associated with more convictions via perceived accuracy. These effects run contrary to some previous literature and, coupled with our findings regarding criminality stereotypes, suggest that prospective jurors may be becoming aware of systemic bias facing Indigenous peoples. This study adds to the growing body of research investigating prospective jurors' decision making in Canada.